Incidence and factors associated with stent dysfunction and pancreatitis after gastroduodenal stenting for malignant gastric outlet obstruction - Yamashige, Daiki; Hijioka, Susumu; Nagashio, Yoshikuni; Maruki, Yuta; Fukuda, Soma; Yagi, Shin; Okamoto, Kohei; Hara, Hidenobu; Hagiwara, Yuya; Agarie, Daiki; Takasaki, Tetsuro; Chatto, Mark; Ohba, Akihiro; Kondo, Shunsuke; Morizane, Chigusa; Ueno, Hideki; Sone, Miyuki; Saito, Yutaka; Okusaka, Takuji (Endoscopy International Open, 2024)
Background and study aims Endoscopic gastroduodenal stent (GDS) deployment is currently a standard treatment for malignant gastric outlet obstruction (mGOO) in patients with limited life expectancy; however, stent dysfunction (SD) and complicated pancreatitis often occur after GDS deployment. We investigated incidence and contributing factors of SD and complicated pancreatitis.Patients and methods We retrospectively reviewed 203 patients who underwent initial GDS deployment for palliation of mGOO symptoms between October 2017 and July 2022, including 109 who underwent GDS deployment across the duodenal papilla (sub-cohort).Results SDs, including tumor ingrowth (n = 26), kinking (n = 14), and migration (n = 13), occurred in 68 patients (33.5%). Cumulative SD incidence was 41.1% (95% confidence interval, 32.6–49.4%). SD incidence increased to 0.4%, 0.16%, and 0.06% per day at < 8, 8–16, and>16 weeks, respectively. On multivariate analysis, Niti-S pyloric/duodenal stent deployment (sub-distribution hazard ratio [sHR] 0.26, P = 0.01) and survival length ≥ 90 days (sHR 2.5, P = 0.01) were respectively identified as favorable and risk factors significantly associated with SD. Pancreatitis developed in 14 patients (12.8%) in the sub-cohort, which had significantly higher parenchymal diameter (P < 0.01) and lower main pancreatic duct (MPD) caliber (P < 0.01) than the non-pancreatitis cohort. On multivariate analysis, MPD caliber < 3 mm independently predicted pancreatitis (odds ratio 6.8, P = 0.03).Conclusions Deployment of the Niti-S pyloric/duodenal stent, with conformability even for angulated strictures, significantly reduced the incidence of SD. Stent selection, life expectancy, and MPD caliber should be taken into consideration during decision-making for GDS deployment for mGOO.
Keywords: Endoscopy Upper GI Tract; Malignant strictures; Dilation, injection, stenting; Pancreatobiliary (ERCP/PTCD); Strictures